Role of Hyperbilirubinaemia as a Predictor of Complicated Appendicitis in Paediatric Population - Dinesh Prasad Koirala; Amit Kumar Gupta; Geha Raj Dahal; Bibek Man Shrestha; Suraj Shrestha; Subita Neupane; Rameshwar Prasad Pokharel (Wolters Kluwer Medknow Publications, 2022)
Background: Acute appendicitis is a common surgical emergency amongst the paediatric population. Available diagnostic tools are focussed to make a diagnosis of acute appendicitis. A definitive predictive factor for the diagnosis of complicated appendicitis is lacking. Thus, this aims to analyse hyperbilirubinaemia as a predictor of complicated appendicitis amongst the paediatric population. Materials and Methods: A prospective observational study was conducted in a tertiary hospital from November 2018 to October 2019. All children undergoing emergency appendectomy were included in the study. Preoperatively, patients were evaluated clinically, and routine investigations including total and direct serum bilirubin were sent. All patients were grouped as 'simple appendicitis' or 'complicated appendicitis' based on intra-operative and histological findings. Bilirubin level was compared between these groups and analysed. Results: A total of 52 children fulfilling the inclusion criteria were included. The mean age was 13.2 ± 4.2 years, and the male: female ratio was 2.1:1. Thirty-four (65.4%) had simple appendicitis and 18 (34.6%) had complicated appendicitis. Total bilirubin was 23.83 ± 5.94 mmol/L in the complicated appendicitis group and 13.15 ± 3.29 mmol/L in the simple appendicitis group. Direct bilirubin was 5.28 ± 2.22 mmol/L in complicated appendicitis and 2.62 ± 0.83 mmol/L in simple one. Both total and direct bilirubin were significantly high in the complicated group (P < 0.001) compared to the simple appendicitis group. On the Receiver operating curve (ROC), the best cutoff value for total and direct bilirubin was 21 and 5.5 mmol/L, respectively. The sensitivity and specificity of total and direct bilirubin were 72.2%, 100%, and 61.1%, and 85.3%, respectively. Conclusion: It is concluded that hyperbilirubinaemia is a good predictor for paediatric complicated appendicitis.